PLURAL CONOTONYMS REFERRING TO CULTURAL FIGURES IN MODERN MEDIA DISCOURSE: SEMANTIC AND FUNCTIONAL POTENTIAL - Slobodian, Tetiana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article analyzes the peculiarities of the functioning of plural conotonyms referring to Ukrainian and Russian cultural figures in the texts of modern electronic media from 2010 to 2025. The study explores the mechanisms of grammatical metaphorization and stylistic deonymization that transform a proper name into a typified category and an image-symbol. A clear semantic differentiation of the onymic field is revealed: the destructive conotonymization of Russian classics as markers of imperial heritage and tools of ideological aggression («pushkins», «bulgakovs») is contrasted with the glorification of the national intellectual pantheon («Shevchenkos», «Stuses»). Particular attention is paid to the graphic codes of decolonization (changes in case / capitalization, the use of quotation marks, and hyphenated compounds) and the role of plural onyms in overcoming the perceived fragmentation of the Ukrainian resistance force. It is proved that the transformation of plural conotonyms in publicistic discourse serves as a reflection of the decolonization of linguistic consciousness and the formation of a sovereign onymic space in Ukraine.